Risk factors for adverse reactions of fundus fluorescein angiography - YangYi; MaiJingzhuang; WangJun (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Background: To explore the difference between the outcomes of correlations between a series of variables and adverse reactions (ARs) to fluorescein from univariate and multivariate analysis and to evaluate the nausea effects in different age groups. Methods: A retrospective study of patients undergoing consecutive fluorescein angiography between March 2010 and February 2012 was conducted. No patients were excluded on the ground of age, presence of atopy, allergy history, previous procedures without severe allergic ARs, asymptomatic hypertension and kidney failure with serum creatinine levels lower than 250 μmol/L or with renal dialysis. Results: A total of 829 patients were enrolled and 22.2% of them had ARs. The majority of reactions were nausea (12.1%) which occurred less when age became old (P Conclusions: Fluorescein angiography is a safe procedure for patients who are relatively healthy but with a history of any systemic disease. Young age, prior reactions and motion sickness which are highly related to emetic events should be considered in the evaluation of ARs to fluorescein.